Adjuvant Treatment with 5‐Fluorouracil and Oxaliplatin Does Not Influence Cardiac Function, Neurovascular Control, and Physical Capacity in Patients with Colon Cancer. (31st August 2020) - Groehs, Raphaela V.; Negrao, Marcelo V.; Hajjar, Ludhmila A.; Jordão, Camila P.; Carvalho, Bruna P.; Toschi‐Dias, Edgar; Andrade, Ana C.; Hodas, Fabiana P.; Alves, Maria J.N.N.; Sarmento, Adriana O.; Testa, Laura; Hoff, Paulo M.G.; et al.
Abstract: Background: Adjuvant chemotherapy with 5‐fluorouracil (5‐FU) and oxaliplatin increases recurrence‐free and overall survival in patients with colon adenocarcinoma. It is known that these drugs have been associated with cardio‐ and neurotoxicity. We investigated the effects of 5‐FU ± oxaliplatin on cardiac function, vascular responses, neurovascular control, and physical capacity in patients with colon cancer. Methods: Twenty‐nine patients with prior colectomy for stage II–III adenocarcinoma and clinical indication for adjuvant chemotherapy were allocated to receive 5‐FU ( n = 12) or 5‐FU + oxaliplatin ( n = 17), according to the oncologist's decision. All the analyses were performed just before and after the end of chemotherapy. Cardiac function was assessed by echocardiography and speckle tracking, and cardiac autonomic control was assessed by heart rate variability (HRV). Vascular endothelial function was assessed by flow‐mediated dilation (FMD). Muscle sympathetic nerve activity (MSNA) was directly recorded by microneurography technique, and muscle blood flow by venous occlusion plethysmography. Physical capacity was evaluated by cardiopulmonary exercise test. Results: Chemotherapy (pooled data) did not significantly change left ventricular ejection fraction (58 ± 1 vs. 55 ± 2%, p = .14), longitudinal strain (−18 ± 1 vs. −18 ± 1%, p = .66), and HRV. Likewise, chemotherapy did not significantly change FMD, muscle blood flow, and MSNA (33 ± 2 vs. 32 ± 1 bursts/min, p = .31). Physical capacity was not significantly changed in both groups. Similar findings were observed when the patients were subdivided in 5‐FU and 5‐FU + oxaliplatin treatment groups. 5‐FU and 5‐FU + oxaliplatin did not significantly change cardiac function, HRV, vascular responses, MSNA, and physical capacity. Conclusion: This study provides evidence that adjuvant treatment with 5‐FU ± oxaliplatin is well tolerated and does not promote changes compatible with long‐term cardiotoxicity. Implications for Practice: Adjuvant chemotherapy with 5‐fluorouracil (5‐FU) and oxaliplatin increases recurrence‐free and overall survival in patients with colon adenocarcinoma; however, these drugs have been associated with cardio‐ and neurotoxicity. This study investigated the effects of these drugs on cardiac function, vascular responses, neurovascular control, and physical capacity in patients with colon cancer. It was found that 5‐FU and oxaliplatin did not significantly change cardiac function, cardiac autonomic control, vascular endothelial function, muscle sympathetic nerve activity, and physical capacity. This study provides evidence that adjuvant treatment with 5‐FU ± oxaliplatin is well tolerated and does not promote changes compatible with long‐term cardiotoxicity. Abstract : This report provides new information about the effect of adjuvant chemotherapy treatment with fluorouracil and oxaliplatin in patients with stage II and III colon cancer.